Answers

2014-07-06T12:26:30+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
So common difference(d) = 51 - 54 = -3
using formula of sum of terms
 s = n/2(2a +(n - 1)d)
here s = sum 
a = first term
n = no . of terms
d = common difference
so
513 = n/2(54 ×2 +(n -1)(-3))
so solving for n we get n = 19 terms
0
2014-07-06T13:21:43+05:30
So common difference(d) = 51 - 54 = -3 using formula of sum of terms  s = n/2(2a +(n - 1)d) here s = sum  a = first term n = no . of terms d = common difference so 513 = n/2(54 ×2 +(n -1)(-3)) so solving for n we get n = 19 terms

0